Polypyrrole-MoS2 Nanopetals as Efficient Anode Material for Lead-Based Hybrid Ultracapacitors. Issue 5 (14th May 2021) - Muduli, Sadananda; Naresh, Vangapally; Pati, Subir K.; Duary, Subrata; Martha, Surendra K.
Abstract : Lead-carbon hybrid ultracapacitors are being a solution to the lead-acid battery to solve issues of sulfation and improve cycle life. In this work, we present polypyrrole-MoS2 –based composite anode material coupled with PbO2 cathode for the lead-carbon hybrid ultracapacitors. Ultracapacitor behavior of polypyrrole-MoS2 based composite shows significant improvement in capacitance and power-density due to the synergetic effect of the high conducting polymer network and redox behavior of MoS2 . The nanopetal shaped composite materials have been synthesized by a simple hydrothermal method at 160 o C by using polypyrrole. The composite Polypyrrole-MoS2 electrode delivers a specific capacitance of 782 Fg −1 at 1 A g −1 current density with low areal specificresistance (1.15 Ohm cm 2 ) in an aqueous H2 SO4 electrolyte. Besides, the PbO2 /Polypyrrole-MoS2 hybrid ultracapacitors deliver capacitance of 285 F g −1 at 5 A g −1 and stable over 10, 000 cycles. The improved capacitive behavior of the Polypyrrole-MoS2 composite electrode is due to the redox behavior, effective intercalation of H + ions into the composite frameworks by transporting the electrons as well as have easy doping/de-doping of sulfate ions to the polypyrrole network.